Estimating the Relationship Between Inflation and Tax Revenues in Selected European Countries: Austria, Germany, France, United Kingdom and Italy - Pyvavar, Iryna; Sokolova, Natalia; Lyashenko, Vyacheslav (My University, 2023)
The state as a special subject of economic relations is constantly in the sphere of influence of various internal and external factors. Among such attributes of doing business, inflation and tax revenues can be distinguished. These metrics are under constant scrutiny. Since it is these attributes that determine the policy of the state in the field of economic relations, and the state can regulate them through its powers and a number of institutional institutions. Thus, the analysis of the dynamics of inflation and tax revenues is an important element in the development of appropriate public policy. The more important point is the study of the relationship between inflation and tax revenues. To solve this problem, we consider a retrospective change in the values of indicators for selected attributes. We also take into account the regional aspect of such interdependence, which is revealed through the analysis of data for different countries. As a research apparatus, we use various statistical methods. We consider the comparative aspect of the obtained results. The paper presents a lot of empirical material in the form of separate graphs and diagrams. This allows a better understanding of the presented analysis. The results obtained can be used to substantiate the strategy of the state's behavior in the sphere of regulation of economic relations.
Keywords: inflation; relationship; tax revenues; dynamics; statistical analysis; regional aspect; retrospective; economic development; economic relations